Apexification and periapical healing of immature teeth using Mineral Trioxide Aggregate - Al-Dahan, Zainab A; Khalaf, Muna S; Al-Assadi, Aseel H (Journal of Baghdad College of Dentistry, 2014)
Background: Apexification is a method to induce a calcified barrier in a root with an open apex or the continued apical development of an incomplete root in teeth with necrotic pulp. MTA apexification has several advantages such as it neither gets resorbed, nor weakens the root canal dentin, and also sets in the wet environment. The aim of this study is to evaluate the effectiveness of the use of MTA in apexification and periapical healing of teeth with incomplete root formation and periapical infection.Materials and method: Apexification was carried out on fourteen permanent immature teeth of eleven children aged 7-12 years attended the teaching hospital of College of Dentistry, Baghdad University using mineral trioxide aggregate followed by obturation of the root canal using gutta percha. The teeth were monitored at 3, 6 and 12 months intervals by clinical examination and radiographical evaluation of root development and healing of periapical lesion. Results: After a 12 months interval, all the teeth appeared to be asymptomatic so that the rate of clinical success in all of the cases was (100%). Radiographically, the success rate was 100% for thirteen teeth while that tooth which was started the treatment with large periapical lesion, showed regression of the periapical destruction suggestive of bone healing and regeneration of the root apex around the MTA material, end with small one so that it started unhealthy but finished with improved healing process. Conclusion: Mineral trioxide aggregate showed both clinical and radiographical success as a material used to induce root-end closure in permanent teeth with immature root formation. This material had the primary advantage of reduction in the number of appointments, development of proper apical seal and healing of periapical lesions.